Through-the-wall radar imaging experiment based on software-defined radio - Zhao, Yuxuan (Nanyang Technological University, 2025)
Wall-Penetrating Radar is a non-destructive testing technology that uses electromagnetic waves to penetrate opaque obstacles for detection, offering significant application potential in detecting concealed targets. With the increasing demand for precise detection technologies in areas such as smart city construction, public safety management, and post-disaster rescue, wall-penetrating radar, as an effective non-invasive detection method, has garnered considerable attention and research. This dissertation presents an in-depth study of Time-Wave Radar Imaging (TWRI), covering its basic principles, system design, optimization methods, and practical applications. Initially, we explore the theoretical foundations of electromagnetic wave propagation and scattering in various media, which serve as the basis for understanding and implementing wall-penetrating radar imaging technology. By analyzing theoretical models, we can better comprehend the interaction between electromagnetic waves and obstacles, providing theoretical support for radar system design in practical applications. Based on this foundation, this dissertation further examines system design and optimization solutions for wall-penetrating radar imaging, covering key aspects such as frequency selection, antenna configuration, and signal processing techniques. We discuss how to select appropriate frequency bands based on specific application needs and optimize antenna design to improve imaging resolution and penetration depth. Additionally, signal processing techniques play a crucial role in enhancing system performance, reducing noise, and mitigating interference, which significantly contributes to the overall system's effectiveness. Software-Defined Radio (SDR) is an innovative technology that performs radio signal processing functions through software rather than traditional hardware. The core idea behind SDR is to transfer as many radio functions as possible to software, leveraging the powerful computational abilities of computer hardware to flexibly handle tasks such as signal modulation, demodulation, and filtering. By updating software, an SDR system can support new communication protocols, frequencies, and signal types without the need for hardware replacement. This dissertation discusses the fundamental concepts, architecture, implementation methods, and broad application areas of SDR, particularly highlighting the advantages of using programmable hardware and general-purpose software to replace the dedicated hardware found in traditional radio systems. The main contribution of this dissertation lies in integrating wall-penetrating radar imaging technology with software-defined radio technology. We conducted a series of experiments using the software-defined radio devices, USRP2954 and USRP2955, developed by National Instruments (NI), to validate the operability and performance of this technology on the SDR platform. In addition, we developed a MATLAB-based wall-penetrating radar imaging algorithm program that efficiently processes experimental data and generates imaging results, providing a convenient means to showcase the imaging effects. Through this research, we not only validate the feasibility of wall-penetrating radar technology but also provide both theoretical and practical support for its broader application in various fields.